The 2021 flexible and printed electronics roadmap. (17th May 2021) - Bonnassieux, Yvan; Brabec, Christoph J; Cao, Yong; Carmichael, Tricia Breen; Chabinyc, Michael L; Cheng, Kwang-Ting; Cho, Gyoujin; Chung, Anjung; Cobb, Corie L; Distler, Andreas; Egelhaaf, Hans-Joachim; Grau, Gerd; et al.
Abstract: This roadmap includes the perspectives and visions of leading researchers in the key areas of flexible and printable electronics. The covered topics are broadly organized by the device technologies (sections 1–9), fabrication techniques (sections 10–12), and design and modeling approaches (sections 13 and 14) essential to the future development of new applications leveraging flexible electronics (FE). The interdisciplinary nature of this field involves everything from fundamental scientific discoveries to engineering challenges; from design and synthesis of new materials via novel device design to modelling and digital manufacturing of integrated systems. As such, this roadmap aims to serve as a resource on the current status and future challenges in the areas covered by the roadmap and to highlight the breadth and wide-ranging opportunities made available by FE technologies.